Needs Analysis for Developing Critical Thinking–Integrated Electronic Worksheets on Particle Dynamics at the Undergraduate Level - Intan Purnama Yani; Ratnawulan; Ahmad Fauzi; Emiliannur (Postgraduate, University of Mataram, 2026)
Particle Dynamics learning requires higher-order thinking skills, particularly critical thinking skills. However, many students still experience difficulties in analyzing problems and drawing appropriate inferences related to physics concepts. This study aims to analyze undergraduate students’ critical thinking skills profiles and examine the need for developing electronic student worksheets (E-Student Worksheets) for Particle Dynamics learning. A quantitative descriptive approach with a descriptive exploratory design was employed. The participants were 61 undergraduate students from a Physics Education program who had completed or were currently taking the Basic Physics course. The participants were selected using purposive sampling because they had prior exposure to Particle Dynamics concepts, making them suitable for critical thinking skills assessment and needs analysis. Data were collected using two instruments: a critical thinking skills test and a needs analysis questionnaire. The critical thinking skills test consisted of open-ended physics problems designed based on Facione’s framework of critical thinking indicators, including interpretation, analysis, evaluation, explanation, and inference. Descriptive statistical analysis using mean scores and percentages was applied to analyze the data. The results indicate that students’ critical thinking skills are generally low, with average scores ranging from 35 to 39 across all indicators, particularly in the areas of analysis and inference. Furthermore, the needs analysis results show that all indicators related to instructional material development fall within the “Needed” category (61–80%), supported by students’ high digital engagement. These findings imply that instructional materials should be designed to provide structured guidance that facilitates students’ reasoning processes in solving Particle Dynamics problems. Therefore, the development of critical thinking–integrated electronic student worksheets is considered urgent and has strong potential to improve the quality of Particle Dynamics learning at the undergraduate level